2023
DOI: 10.3390/ijms241511876
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic–Phenotypic Correlations of Hereditary Hyperferritinemia-Cataract Syndrome: Case Series of Three Brazilian Families

Olivia A. Zin,
Luiza M. Neves,
Daniela P. Cunha
et al.

Abstract: Hereditary hyperferritinemia-cataract syndrome (HHCS) is a rare, frequently misdiagnosed, autosomal dominant disease caused by mutations in the FTL gene. It causes bilateral pediatric cataract and hyperferritinemia without iron overload. The objective of this case series, describing three Brazilian families, is to increase awareness of HHCS, as well as to discuss possible phenotypic interactions with concurrent mutations in HFE, the gene associated with autosomal recessive inheritance hereditary hemochromatosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…showed that genetic testing in bilateral pediatric patients avoided unnecessary tests in 50% of them (10). As an example, one patient from our cohort had unnecessary phlebotomies and used prolonged oral iron chelator for having hyperferritinemia, which was then diagnosed as hereditary hyperferritinemia-cataract syndrome after genetic testing (19).…”
Section: Discussionmentioning
confidence: 88%
“…showed that genetic testing in bilateral pediatric patients avoided unnecessary tests in 50% of them (10). As an example, one patient from our cohort had unnecessary phlebotomies and used prolonged oral iron chelator for having hyperferritinemia, which was then diagnosed as hereditary hyperferritinemia-cataract syndrome after genetic testing (19).…”
Section: Discussionmentioning
confidence: 88%